(untitled) (Research in Agriculture Livestock and Fisheries, 2022)
The study was conducted in agricultural research field at Noakhali Science and Technology University, Noakhali, Bangladesh during March 2021 to enhance the production of red amaranth (Amaranthus gangeticus cv: RM) by using urea fertilizer with gibberellic acid. The experiment was laid out in a Randomized Complete Block Design (RCBD) comprising four treatments with three replications. The treatment combinations were T0 (Urea 0 kg ha-1 and 0 ppm GA3), T1 (Urea 200 kg ha-1), T2 (60 ppm GA3), T3 (Urea 200 kg ha-1 and 60 ppm GA3), respectively. The growth and yield characters of red amaranth showed significant variation for different treatments of urea and gibberellic acid. The maximum plant height (37.1 cm), leaf number (13.83), leaf breadth (4.8 cm), leaf length (8.0 cm), shoot diameter (0.583 cm), fresh plant weight (9.73 g), dry weight per plant (0.775 g), yield per hectare (15.58 t/ha) were measured from treatment T3 (urea fertilizer + gibberellic acid) at harvest (22 days after sowing). The maximum benefit cost ratio (BCR = 3.653) was recorded from treatment T3 (urea fertilizer + gibberellic acid). Thus, it is concluded that the combined application of urea fertilizer with gibberellic acid would be optimum for short term growth and better yield of red amaranth. Vol. 9, No. 2, August 2022: 97-102